Nucleus-Encoded Genes for Plastid-Targeted Proteins in Helicosporidium: Functional Diversity of a Cryptic Plastid in a Parasitic Alga - de Koning, Audrey P. (American Society for Microbiology, 2004)
Plastids are the organelles of plants and algae that house photosynthesis and many other biochemical pathways. Plastids contain a small genome, but most of their proteins are encoded in the nucleus and posttranslationally targeted to the organelle. When plants and algae lose photosynthesis, they virtually always retain a highly reduced “cryptic” plastid. Cryptic plastids are known to exist in many organisms, although their metabolic functions are seldom understood. The best-studied example of a cryptic plastid is from the intracellular malaria parasite, Plasmodium, which has retained a plastid for the biosynthesis of fatty acids, isoprenoids, and heme by the use of plastid-targeted enzymes. To study a completely independent transformation of a photosynthetic plastid to a cryptic plastid in another alga-turned-parasite, we conducted an expressed sequence tag (EST) survey of Helicosporidium. This parasite has recently been recognized as a highly derived green alga. Based on phylogenetic relationships to other plastid homologues and the presence of N-terminal transit peptides, we have identified 20 putatively plastid-targeted enzymes that are involved in a wide variety of metabolic pathways. Overall, the metabolic diversity of the Helicosporidium cryptic plastid exceeds that of the Plasmodium plastid, as it includes representatives of most of the pathways known to operate in the Plasmodium plastid as well as many others. In particular, several amino acid biosynthetic pathways have been retained, including the leucine biosynthesis pathway, which was only recently recognized in plant plastids. These two parasites represent different evolutionary trajectories in plastid metabolic adaptation.